Effect of nutrients and organic substances on growth and quality attributes of apple (Malus × domestica) cv. Anna insemi-arid region of Haryana - JAT, MOHAN LAL; RANA, G S; SHIVRAN, JITENDRA SINGH; JAT, R K; MOR, RAJESH; KUMARI, SANTOSH; MEHTA, GAGAN; GAVRI, ANKIT (The Indian Journal of Agricultural Sciences, 2024)
An experiment was conducted during 2020–21 and 2021–22 at Horticulture farm of Chaudhary Charan Singh Haryana Agricultural University, Hisar, Haryana to study the effect of different plant nutrients and organic substances on growth, flowering, quality and yield attributes of the apple (Malus × domestica Borkh) cultivar Anna. The experiment consists of 19 treatments laid out in a randomized block design. Among the various treatments used, T12 (2.0% nitrogen plus 15% cow urine) was found superior for the growth characteristics of plants, viz. plant height (2.87 m) and plant spread (3.02 m). However, the number of days taken for flowering (70.83), fruit set (19.72 %), fruit weight (177.68 g), fruit diameter (6.40 cm), yield (11.25 kg/plant), TSS (11.45 °Brix), acidity (0.51%), total sugars (10.01%), total phenol (70.72 mg GAE/g), total anthocyanin (19.11 mg/100 g) and total carbohydrate (155.55 mg/g) content were significantly influenced by treatment T6 (400 ppm Boron + 4% Humic acid) during both the years.